If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + 18p = 8p Combine like terms: 5p + 18p = 23p 23p = 8p Solving 23p = 8p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-8p' to each side of the equation. 23p + -8p = 8p + -8p Combine like terms: 23p + -8p = 15p 15p = 8p + -8p Combine like terms: 8p + -8p = 0 15p = 0 Divide each side by '15'. p = 0 Simplifying p = 0
| 71=5x-2(-2x-4) | | 12a^3-26a^2+12a=0 | | 6x-5(-3x+3)=195 | | 40a+16=56 | | 48a+16=28 | | 3(7-2x)=27 | | 12x-28=28 | | 12000*x^8=15201.24 | | 28=y/4-11 | | 94=5x+9 | | 4a^3+8a^2-a=221 | | -12x+28=2x-3 | | 3(x-4)=7x-10-4x | | 2x+8=8(x+1)-6x | | M+122=188 | | 9*x=500 | | 3x+72=8(x+9)-5x | | 4*x=500 | | 3x-(9x+5)=15-6x | | 25+10-3*20-14= | | x^2-7x=-49 | | x-2y-5z=3 | | 12=6+21x | | 2(5-3r)=-4r-6 | | 6(3x+5)-(18x+5)=25 | | 2/9(-6/5)= | | A=1/6πs^2n | | 2(4d-5)=-26 | | 2/9*(-6/5)= | | 6x+2y-3z=2 | | 3x-2+5x+5=118 | | F(x)=-7+5x^2+10 |